Fate of lead, copper, zinc and antimony during chemical looping gasification of automotive shredder residue. (15th October 2021) - Staničić, Ivana; Cañete Vela, Isabel; Backman, Rainer; Maric, Jelena; Cao, Yu; Mattisson, Tobias
Highlights: Fate of Pb, Cu, Zn and Sb in chemical looping gasification of ASR. Thermodynamic calculations utilized and compared with experimental data. Surface characteristics studied using x-ray photoelectron spectroscopy. Cu/Zn-ferrites, Pb-silicates and Sb-oxides observed on particle surfaces. It is found that iron plays an important role in this complex chemistry. Abstract: Gasification experiments in this study were performed in a 2–4 MW indirect gasifier coupled to a semi-commercial CFB combustor at Chalmers University of Technology. Experiments were carried out during 13 days with automotive shredder residue (ASR), giving a unique opportunity to investigate the bed material under realistic conditions and with long residence times. The metal rich ash was accumulated in the bed, gaining some oxygen carrying capabilities, creating a chemical looping gasification (CLG) process. This study aims to expand the knowledge about the chemistry of zinc, copper, lead and antimony during CLG of ASR. Several experimental methods have been utilized, such as XRD, SEM-EDX and XPS along with detailed thermodynamic calculations to study chemical transformations that can occur in the system. Thermodynamic calculations showed that the reduction potential affect the phase distribution of these elements, where highly reduction conditions result in heavy metals dissolving in the slag phase. Copper and zinc ferrites, lead silicates and antimony oxides were identified at the particle surfaces in the bottom ash. The formation of an iron rich ash layer plays an important role, especially for copper and zinc speciation. The main pathways in the complex CLG system have been discussed in detail.